KONTEN IKLAN YANG RAMAH WISATAWAN MILENIAL - Hakim, Imam Nur (Jurnal Pariwisata Pesona, 2020)
The significant increase of millennial tourist trips makes the Indonesian tourism sector consider it as a market opportunity. Consequently, stakeholders must adjust their development policies with the characteristics of the millennial tourist market, including marketing and advertising domains. As a Stakeholder, Destination Management Organization (DMO) needs to change the way they advertise, including determining the content that fits millennial preferences. Through a descriptive qualitative approach, this paper combines millennial characteristics with their travel habits, to form content that is friendly to millennial tourists. The results of this study showed that advertisement content should be; focus on experience over tourism destination; is presented simple and organic; use the price approach; take advantage of eWoM's reputation; focus on social impacts in local life.